Proust and America - Murphy, Michael 1965-2009
"It is strange," Proust wrote in 1909, "that, in the most widely different departments ... there should be no other literature which exercises over me so powerful an influence as English and American." In the spirit of Proust's admission, this engaging and critical volume offers the first comparative reading of the French novelist in the context of American art, literature, and culture. In addition to examining Proust's key American influences--Ralph Waldo Emerson, Edgar Allan Poe, and James McNeill Whistler--Proust and America investigates the previously overlooked influence of the American neurologist George Beard, whose writings on neurasthenia and "American nervousness" contributed to the essential modernity of the author's work
Keywords: Art américain; Art et littérature; Art and literature; Art, American; LITERARY CRITICISM; Literary studies: fiction, novelists and prose writers; Literature and literary studies; Literature: history and criticism; literature; proust; Proust, Marcel / 1871-1922 / À la recherche du temps perdu; À la recherche du temps perdu (Proust, Marcel); Electronic books; Biography; Biographies